Activity of clarithromycin alone or in combination with other drugs for treatment of murine toxoplasmosis. - Araujo, F G (1992)
The activity of the macrolide antibiotic clarithromycin was examined alone or in combination with other drugs for the treatment of acute or chronic infections with Toxoplasma gondii in mice. A dose of 300 mg of clarithromycin per kg per day administered alone for 10 days, beginning 24 hours after infection, protected 10 to 30% of mice infected with lethal inocula of tachyzoites or tissue cysts of different strains of T. gondii, including some strains isolated from patients with both AIDS and toxoplasmosis. Although clarithromycin was protective, a wide variation in its activity against different strains was observed. Survival of infected mice was increased significantly by treatment with clarithromycin in combination with pyrimethamine or with sulfadiazine. Treatment of chronically infected mice with clarithromycin at 300 mg/kg/day administered alone for 8 weeks resulted in significant reduction in the numbers of T. gondii cysts in their brains. The combination of clarithromycin and minocycline resulted in an activity against T. gondii cysts that was significantly greater than the activity of clarithromycin or minocycline administered alone. These results indicate a role for clarithromycin in the treatment of human toxoplasmosis, particularly when this antibiotic is used in combination with other drugs with activity against T. gondii.